Споредбена анализа на македонски и на чешки фраземи со компонента рај/пекол - Jasminka Delova-Siljanova (Univerzita Komenského v Bratislave, 2019)
Comparative analysis of Macedonian and Czech idioms with components Paradise/Hell The research topic in this paper are Macedonian and Czech idioms from the area of religion. The purpose of the analysis is to identify similarities and differences in the way that Macedonians and Czechs perceive those terms through the axiological values contained in the idioms.